Atmospheric Stabilization of CO2 Emissions : Near-term Reductions and Intensity-based Targets - Timilsina, Govinda R. (World Bank, Washington, DC, 2012)
This study analyzes CO2 emissions reduction targets for various countries and geopolitical regions by the year 2030 in order to stabilize atmospheric concentrations of CO2 at the level of 450 ppm (550 ppm including non CO2 greenhouse gases). It also determines CO2 intensity cuts that would be needed in those countries and regions if the emission reductions were achieved through intensity-based targets while assuming no effect on forecasted economic growth. Considering that the stabilization of CO2 concentrations at 450 ppm requires the global trend of CO2 emissions to reverse before 2030, this study develops two scenarios: reversing the global CO2 trend in (i) 2020 and (ii) 2025. The study shows that global CO2 emissions would be 42 percent above the 1990 level in 2030 if the increasing trend of global CO2 emissions is reversed by 2020. If reversing the trend is delayed by 5 years, the 2030 global CO2 emissions would be 52 percent higher than the 1990 level. The study also finds that to achieve these targets while maintaining assumed economic growth, the global average CO2 intensity would require a 68 percent drop from the 1990 level or a 60 percent drop from the 2004 level by 2030.